2017
DOI: 10.1016/j.jss.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine activates the Akt pathway to upregulate extracellular matrix protein production in human aortic valve cells

Abstract: Background Overproduction of extracellular matrix (ECM) protein by aortic valve interstitial cells (AVICs) plays an important role in valvular sclerosis (thickening) associated with the early pathobiology of aortic stenosis. Accumulation of oxidized low-density lipoprotein (oxLDL) is observed in sclerotic aortic valve and may have a mechanistic role in valvular disease progression. Lysophosphatidylcholine (LysoPC) is a component of oxLDL and has multiple biological activities. Objective This study was to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…A number of studies have demonstrated that the Akt/mTOR signaling cascade is associated with cardiac hypertrophy [34, 35]. Akt is also involved in regulating the ability of oxidized low-density lipoprotein and lysophosphatydylcholine in the upregulation of ECM protein production in human aortic valve interstitial cells [36]. Accumulation of ECM proteins may contribute to the mechanism of valvular sclerosis associated with the development and progression of aortic stenosis [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that the Akt/mTOR signaling cascade is associated with cardiac hypertrophy [34, 35]. Akt is also involved in regulating the ability of oxidized low-density lipoprotein and lysophosphatydylcholine in the upregulation of ECM protein production in human aortic valve interstitial cells [36]. Accumulation of ECM proteins may contribute to the mechanism of valvular sclerosis associated with the development and progression of aortic stenosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Akt is also involved in regulating the ability of oxidized low-density lipoprotein and lysophosphatydylcholine in the upregulation of ECM protein production in human aortic valve interstitial cells [36]. Accumulation of ECM proteins may contribute to the mechanism of valvular sclerosis associated with the development and progression of aortic stenosis [36]. PI3K/Akt signaling was reported to modulate the NF-ĸB pathway and its downstream target IL-6 which in turn affected the calcification process of VICs [37].…”
Section: Discussionmentioning
confidence: 99%
“…LPC has been shown to stimulate Akt signaling pathway to up-regulate the production of extracellular matrix proteins such as biglycan, and type I collagen in human aortic valve cells [ 30 ]. But this effect of LPC is not mediated by MEK/ERK signaling [ 30 ]. These effects by LPC may contribute to valve sclerosis as well as aortic stenosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…But this effect of LPC is not mediated by MEK/ERK signaling [ 30 ]. These effects by LPC may contribute to valve sclerosis as well as aortic stenosis [ 30 ]. Limited information is known about the effect of LPC on PI3K/Akt signaling of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown from this study whether NT3 induces myofibroblastic transition in human AVICs to elevate their fibrogenic activity. Our previous studies found that soluble matrilin 2 upregulates α-smooth muscle action (α-SMA) levels and elevates the fibrogenic activity in human AVICs [35], while ox-LDL elevates human AVIC fibrogenic activity without the upregulation of cellular levels of α-SMA [36]. It appears that the induction of myofibroblastic transition in human AVICs is stimulus-specific and that either cell activation or cell phenotype transition may elevate human AVIC fibrogenic activity.…”
Section: Discussionmentioning
confidence: 99%